2016
DOI: 10.1080/09540121.2016.1140890
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic and clinical factors explaining the risk of unstructured antiretroviral therapy interruptions among Kenyan adult patients

Abstract: A cross-sectional study was conducted to assess the extent of unstructured HIV treatment interruptions (TIs) and investigate the effects of socioeconomic, socio-demographic, HIV treatment-related and clinical factors on the magnitude and rate of the same among adult patients at a Kenyan regional referral center. Four hundred and twenty-one adult patients actively receiving antiretroviral therapy at Nyeri County Referral Hospital since 2003 were randomly selected to complete a health survey questionnaire. Elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…These people are therefore likely to have NNRTI drug resistance. 33 , 34 , 35 Nevertheless, model outputs for the proportion of ART initiators with NNRTI pretreatment drug resistance who have previous antiretroviral drug exposure were not substantially higher than for those who have no previous antiretroviral drug exposure, which is in contrast with survey findings of pretreatment drug resistance that show markedly higher levels. This implies an even greater tendency for interruption of ART to be more likely in those with poor adherence than was assumed, which might imply that the policies just targeted at those with previous antiretroviral drug exposure could be more effective than we have shown.…”
Section: Discussionmentioning
confidence: 65%
“…These people are therefore likely to have NNRTI drug resistance. 33 , 34 , 35 Nevertheless, model outputs for the proportion of ART initiators with NNRTI pretreatment drug resistance who have previous antiretroviral drug exposure were not substantially higher than for those who have no previous antiretroviral drug exposure, which is in contrast with survey findings of pretreatment drug resistance that show markedly higher levels. This implies an even greater tendency for interruption of ART to be more likely in those with poor adherence than was assumed, which might imply that the policies just targeted at those with previous antiretroviral drug exposure could be more effective than we have shown.…”
Section: Discussionmentioning
confidence: 65%
“…Not only does the relationship with HCP affect adherence/non-adherence, but also socioeconomic factors such as higher income, occupation, education level, and disease-related factors such as more symptoms and the duration of ART. Studies have shown regional distinctions in the impact of these different factors, which seem to play a decisive role in African countries [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The model is not applicable to situations where a patient does not have continuous access to ARVs. Lack of access might occur for reasons of pharmacy stock shortages, individual resource constraints, or other circumstances [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%